Gender disparity in mass media exposure in Uttar Pradesh, India: an analysis of the NFHS 2019-21 data - Singh , Ananya; Singh , Mayank Kumar; Narayan , Raj; Chauhan , Alok; Adichwal , Nitesh Kumar; Mishra, Rohan (Brazilian Journal of Biometrics, 2026)
Mass media refers to any communication platform that reaches large audiences and is used to inform, entertain, and educate people. Ideally, access to mass media should be distributed equally across all sections of society, regardless of gender, caste, economic status, religion, place of residence, or level of education. Yet, only a limited number of studies—particularly those using recent data—have examined this issue. The present study specifically investigates exposure to mass media among individuals who reported using at least one of the following—radio, television, newspapers, or magazines at least once a week. The data for this study was obtained from the National Family Health Survey (2019–21) among 15–49 years age group. Logistic regression model was performed to assess the gender differences for men and women. In hierarchical regression model, background (age, caste, religion and marital status) were entered on the first step, place of residence (urban/rural) on the second, education on the third and wealth index on the fourth step. Analysis reveals that only 41.7 percent women and 52.1 percent men aged 15–49 years were regularly exposed to the mass media in Uttar Pradesh, India. Majority of the respondents (39.1 percent of women and 42 percent of men) were exposed to television in the age group 15-49. The finding indicated that regular media exposure is significantly less among women as compared to men (AOR = 0.71, 95% CI:0.68–0.74). Women who received twelve or more years of education were 2.8 times (AOR = 2.80, 95% CI:2.67–2.93) more likely to be exposed to mass media as compared to the category of no education whereas men were about 5.4 times more likely to be exposed towards mass media (AOR = 5.43, 95% C.I:4.69–6.30). Furthermore, women in the rich wealth index were 5.4 times more likely (AOR = 5.38, 95% C.I:5.2–5.6) to be exposed but men were only 3.4 times (AOR = 3.31, 95% CI:2.96–3.70) exposed to mass media compared to the poor wealth index. However, rural women had lower odds of mass media exposure than urban (AOR=0.66, 95% CI:0.63–0.69), rural men had lower likelihood of mass media exposure than urban men (AOR=0.67, 95% CI:0.60–0.76). The study demonstrates that men are more likely than women to be exposed towards mass media in Uttar Pradesh, India. The findings of this paper provide evidence that education level and wealth index were the main significant predictor variables for gender differences towards overall mass media exposure. It suggests that greater focus must be placed on the marginalized population, especially women.